Co-occurrence of trichotillomania and polycystic ovarian syndrome: A case report / Ismaliza Ismail ... [et al.] - Ismail, Ismaliza; Wan Ismail, Wan Salwina; Md. Nor, Norazirah; Lee, Voon Yee; Zainuddin, Ani Amelia (Universiti Teknologi MARA Cawangan Selangor, 2020)
Trichotillomania (TTM) or hair pulling disorder is characterized by repetitive pulling of hair on the body whereas Polycystic Ovarian Syndrome (PCOS) is a metabolic-endocrine disorder, manifested by irregular menstrual cycle and clinical hyperandrogenism. Both disorders commonly occur in young females. TTM and PCOS may be related and share the same pathophysiology. We reported a case of a teenager with TTM and PCOS, which were triggered by stress. Neurobiological mechanism may explain the co-occurrences between TTM and PCOS. Further research in the neurobiology of TTM and PCOS may better explain the co- occurrences between the two disorders.